2013
DOI: 10.1039/c2cp42933k
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of key domains in complete adsorption of Aβ peptide on single-walled carbon nanotubes: insights with point mutations and MD simulations

Abstract: Owing to the influence of nanomaterials on biomacromolecular behavior, their potential applications are rapidly gaining attention. Based on atomistic molecular dynamics simulation studies we have recently reported that the full-length Aβ peptide, whose self-assembly is associated with Alzheimer's disease, adsorbs rapidly on single-walled carbon nanotubes, thereby losing its natural propensity to collapse. Here, we investigate the mechanistic overlap between the peptide's compactification and its adsorption, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…23,24 However, structural information on the monomeric and various self-assembled forms has been obtained via NMR methods. [35][36][37][38][39] Kim and Lee rst showed that 1,2-(dimethoxylmethano) fullerene specically binds to the KLVFF region of the Ab protein, thereby suppressing Ab aggregation. 7,18,[26][27][28][29][30] Non-covalent interactions arising from various nanomaterials could be harnessed for modulating the intrinsic selfassembly characteristics of Ab.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, structural information on the monomeric and various self-assembled forms has been obtained via NMR methods. [35][36][37][38][39] Kim and Lee rst showed that 1,2-(dimethoxylmethano) fullerene specically binds to the KLVFF region of the Ab protein, thereby suppressing Ab aggregation. 7,18,[26][27][28][29][30] Non-covalent interactions arising from various nanomaterials could be harnessed for modulating the intrinsic selfassembly characteristics of Ab.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of nanoparticles for the treatment of proteinaggregation diseases is an important one among these applications. [23][24][25][26] But researches on the interaction between Au NPs and Ab proteins have not been reported yet, due to the computationally huge simulations required to simulate all the NP atoms, especially for large NPs. [10][11][12][13][14][15][16][17][18][19][20][21][22] By now, the phenomena of the inuence of Au NPs on the Ab protein aggregations has already been reported using various techniques such as scanning electron microscopy, transmission electron microscopy, atom force microscopy and optical spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…13,[52][53][54][55][56][57] In this study, using fully atomistic molecular dynamics (MD) simulations, we have studied the conformational and dynamical implications of a minor perturbation of H1 interactions, namely the loss of a single side chain-side chain hydrogen bond Y149-D202, that links H1 with the rest of the globular domain of PrP C . 13,[52][53][54][55][56][57] In this study, using fully atomistic molecular dynamics (MD) simulations, we have studied the conformational and dynamical implications of a minor perturbation of H1 interactions, namely the loss of a single side chain-side chain hydrogen bond Y149-D202, that links H1 with the rest of the globular domain of PrP C .…”
mentioning
confidence: 99%